Similarities and convergence in G-7 cycles - Fabio Canova; Matteo Ciccarelli; Eva Ortega (European Central Bank (ECB), 2004)
This paper examines the properties of G-7 cycles using a multicountry Bayesian panel VAR model with time variations, unit specific dynamics and cross country interdependences. We demonstrate the presence of a significant world cycle and show that country specific indicators play a much smaller role. We detect di?erences across business cycle phases but, apart from an increase in synchronicity in the late 1990s, find little evidence of major structural changes. We also find no evidence of the existence of an Euro area specific cycle or of its emergence in the 1990s.
Keywords: C11; C33; E32; 330; Bayesian methods; business cycle; indicators; panel data